ESCHERICHIOSIS INFECTION IN SHEEP ESCHERICHIA COLI - Sarimsakov G.S (Western European Studies, 2024)
The article presents studies of infection from the first days of life of lambs and the course of the disease. Clinical signs, pathoanatomical autopsy are presented. Changes in lymph nodes and parenchymal organs, growth and development during bacteriological studies. Serogroup strains have been isolated
Keywords: Pathoanatomy; lymph; parenchyma; bacteriology